A portable robotic rehabilitation system towards improving impaired function of the hand due to stroke - Opiyo, Albert (Division of Biomedical Engineering, 2017)
Background: Stroke is the leading cause of adult disability with 70 to 85% of initial strokes resulting in hemiparesis. Physical imparity as a result of stroke tends to be severe and majority of impairments are upper limb-related. Impairment is usually accompanied by long term functional loss which requires dedicated post-stroke rehabilitation to regain motor function. The incidence of stroke is increasing rapidly while there remains a shortage of therapists to provide sufficient rehabilitation. There is therefore a high demand for therapists to attend to the rising number of stroke survivors. Robot-aided therapy has emerged as a beneficial tool for providing continuous rehabilitation of the upper limb and is widely being implemented. With this technology, there is great potential to reduce the ill-effects brought about by the low therapist-patient ratio which has hindered sufficient rehabilitation and consequently the effective recovery of motor function among stroke survivors. Hypothesis: The use of a portable robotic rehabilitation system, as a complementary tool, in hand therapy, would promote continuous rehabilitation by encouraging repetition of task oriented exercises which would enhance motor function of an impaired hand. Task-oriented writing practice would potentially improve hand coordination and result in better accuracy while repetitive training would potentially increase hand motor strength. Objectives: 1.To design and manufacture a portable robotic rehabilitation system. 2. To test the performance and usability of the system. Methods: The system was manufactured and its performance tested in a pilot pre-clinical trial involving three participants. The system's ease of use was assessed using a standardised usability scale. Writing accuracy and hand motor strength were also assessed and the results analysed at the end of the study. Results: The average overall score of usability for the rehabilitation system was a few points higher than the average score. The users of the system also experienced increased motivation whilst performing the repetitive and task oriented exercises. There was an improvement in the completion time of the writing accuracy test and the tasks of the trace sample test. The variation in grip strength of the non-dominant hand during the rehabilitation period was small for each of the participants. Conclusion: The rehabilitation system motivated its users to repetitively perform rehabilitative training which may have improved writing accuracy.